Air pollution and public finance: evidence for European countries. Issue 7 (11th November 2019) - Carratù, Maria; Chiarini, Bruno; D'Agostino, Antonella; Marzano, Elisabetta; Regoli, Andrea
Abstract : Purpose: The purpose of this paper is to investigate whether a statistically significant relationship exists between environmental quality, as measured by consumption-related air pollution, and public debt in Europe. In addition, since the debt burden is one of the most important indicators of fiscal soundness within the European Union (EU) Treaty and the subsequent fiscal compact, the authors propose a simple test to determine whether participation in EU Treaties has shaped the empirical relationship between fiscal policy/public debt and environmental performance. Design/methodology/approach: To this end, the authors built a panel data set that covers 24 European countries over the period 1996 – 2015. Findings: The aspect that the authors want to underline is a possible trade off, which is confirmed in the empirical analysis, between the public finance equilibrium and the maintenance of a public good such as air quality. However, there are important non-linearities that shape the interaction between public debt and environmental pollution. Similarly, threshold effects arise when the authors examine the interaction between EU regulation and public debt and when the authors separately examine high debt and low debt countries. When the authors account for the stabilization rules introduced by EU Treaties, a negative effect on pollution is evident; in this way, fiscal consolidation limits the positive effect of fiscal policy. Practical implications: The results point out the existence of a potential trade-off between the role of EU as a regulator aiming to mitigate environmental pollution, and its role within the Stability and Growth Pact. The analysis highlights that fiscal consolidation policies, while facilitating the achievement of macroeconomic stability within EU, might have a negative side effect on the environment quality, which spreads beyond the borders of one single country. Originality/value: While a number of studies have suggested that fiscal spending might contribute to the level of pollution in European countries, there is scant evidence of the effect of public debt on environmental performance. This lack of scientific knowledge is a serious shortcoming, since it may allow for an underrepresentation of the wide-ranging consequences of stabilization programmes targeting the debt-to-GDP ratio, which could affect environmental quality.